Penggunaan Media "Smart Card" pada Kegiatan Penyuluhan Pencegahan Penyakit ISPA untuk Siswa SD Negeri di Tegalrejo, Kota Yogyakarta - Scarvia Nuzula; Siti Hani Istiqomah; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
Knowledge about environmental based diseases prevention, such as acute respiratory infection (ARI), should be given to high-risk groups, e.g. elementary school children. Counseling can achieve its maximum results if the media used is suitable with the target audience. For elementary school students, one of the appropriate media is those that will facilitate them in receiving the health messages given. One of those media is pictorial card named "smart card". The research is a quasi experiment with non-randomized control group pre-test post-test design. The study subjects consisted of 41 grade 4 and 5 students of Pingit Elementary School as the experiment group, and 41 grade 4 and 5 students of Karangrejo elemnetary school as the control group. Results of the statistical analysis using independent t-test at 95 % significance level, obtained a p-value of 0,015. It indicates that the difference in knowledge improvement between those two groups are significant. To conclude, the use of "smart card" in counseling activity influences students’ knowledge about ARI prevention, because the media supports the delivery of of the counseling messages to be received properly by the students.